SaveSmile: an annual cleft repair mission in Sudan - Maarya Akmal; Rhea Zahir; Zain Zahir; Junaid Ahmed; Tarannum Lateef (Journal of Global Health Reports)
Low- and middle-income countries (LMICs) are often burdened by disease, beyond the scope of their healthcare capabilities. Sudan, in particular, lacks the resources and expertise to surgically repair orofacial clefts. This paper highlights Sudan's need for medical aid from other countries and outside organizations and the procedures by which they collaborate with local entities to provide relief to those affected by cleft in Sudan. Additionally, this study reports on the prevalence of type of cleft lip and palate as well as rates and explanations of surgical complications over a period of 10 years and the short and long-term benefits to society. Paper copies of patient data was digitalized and run through statistical programs to look for patterns of demographics and diagnoses. Most patients were male, under four years old, and had a cleft lip.